MicroRNA-222 Expression and Its Prognostic Potential in Non-Small Cell Lung Cancer - Kai-ping Mao; Wei-na Zhang; Xiao-min Liang; Yu-rong Ma (The Scientific World Journal)
Overexpression of miR-222 has been found in several types of cancers; however, the expression of miR-222 in non-small cell lung cancer (NSCLC) and its prognostic values are unclear. This study aimed to investigate whether the miR-222 expression level is related to clinicopathological factors and prognosis of NSCLC. Through a prospective study, 100 pairs of NSCLC tissues and adjacent normal tissues were examined by quantitative reverse-transcription polymerase chain reaction. The correlation between miR-222 expression and clinicopathological features was analyzed, and the significance of miR-222 as a prognostic factor and its relationship with survival were determined. Results showed that the expression levels of miR-222 were significantly elevated in the NSCLC tissue compared with that in adjacent normal tissue. In addition, Cox’s proportional hazards model analysis confirmed that miR-222 high expression level was an independent predictor of poor prognosis. In conclusion, miR-222 overexpression is involved in the poor prognosis of NSCLC and can be used as a biomarker for selection of cases requiring especial attention.